Altered Coronary Flow Velocity Reserve and Left Ventricular Wall Motion Dynamics: A Phenomenon in Hypertensive Patients with ECG Strain. Issue 6 (11th January 2013) - Arita, Yu; Hirata, Kumiko; Wada, Nozomi; Komukai, Kenichi; Tanimoto, Takashi; Kitabata, Hironori; Takarada, Shigeho; Nakamura, Nobuo; Kubo, Takashi; Tanaka, Atsushi; Imanishi, Toshio; Akasaka, Takashi
<x xml:space="preserve">Abstract</x> Background The inner‐half layer of the left ventricular (LV) wall is primarily affected by ischemia and increased LV afterload. We hypothesized that LV wall thickening of inner‐half layer and coronary microvascular function are impaired in hypertensive patients, especially in those with electrocardiographic (ECG) strain, which is a marker of LV hypertrophy and adverse prognosis. Therefore, the aim of this study is to investigate the association of the ratio of inner‐ to outer‐half layer of the LV myocardial deformation and coronary microvascular function with ECG strain in hypertensive patients. Methods We studied 98 hypertensive patients and 13 controls. Hypertensive patients were divided into 2 groups, with (S+) and without (S−) ECG strain. Coronary flow velocity reserve (CFVR) of the left anterior descending artery was evaluated using transthoracic echocardiography. Circumferential and radial strains of the LV wall were analyzed by two‐dimensional echocardiographic speckle tracking method, and the inner‐ to outer‐half layer ratio (in/out ratio) was assessed. Results Coronary flow velocity reserve of S+ (2.06 ± 0.65) was significantly smaller than those in S− and controls (3.03 ± 0.65 and 3.38 ± 0.51, respectively). In/out ratio in both circumferential and radial strains were decreased as well as in S+ patients. Furthermore, in/out ratio was directly proportional to CFVR. Conclusions Hypertensive patients with ECG strain possessed severely impaired CFVR and inner‐half myocardial deformation. Moreover, the more severe the LV hypertrophy progresses, the greater is the impairment of coronary microvascular and LV inner‐half myocardial deformation. Thus, CFVR and in/out ratio are useful quantitative markers that can render sensitive assessment of physiological changes in hypertensive heart disease.